If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3h + 2p = 26 Solving 3h + 2p = 26 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2p' to each side of the equation. 3h + 2p + -2p = 26 + -2p Combine like terms: 2p + -2p = 0 3h + 0 = 26 + -2p 3h = 26 + -2p Divide each side by '3'. h = 8.666666667 + -0.6666666667p Simplifying h = 8.666666667 + -0.6666666667p
| 1+2b=b-1-3 | | 0.25x=29.5 | | 8x-9=6x-19 | | 9x+9=12x+12 | | 58n=172 | | 40000a+200b=6 | | a-18=22 | | 172=58n | | 3xover+8=5 | | 2.3x^2-1.9x=6.8 | | -4x+-12=2x+24 | | -2(4g)= | | 10000a+100b+4.7=8.7 | | 3/x-2/y | | .25x^2+x=-1 | | 13x-4=12x-6 | | 5x+1=2.2 | | 112-15=b | | 13x-7=5x-47 | | 12x+10=5x+24 | | 3x-12=9x-72 | | 9x+4=5.8 | | S/6-12=-16 | | 2+r=5 | | 3.3x+5.7y-6.7=0 | | 4x-11=10x-11 | | 4.25x+3=-3x^2 | | 3x+5=10x-30 | | (3.5x)+x=100 | | √8/21 | | 13x-9=8x-34A-5B-4C-2D-7E-1 | | 7x-11=8x-14 |